2017
DOI: 10.18632/oncotarget.20977
|View full text |Cite
|
Sign up to set email alerts
|

Selecting lncRNAs in gastric cancer cells for directed therapy with bioactive peptides and chemotherapy drugs

Abstract: Selecting lncRNAs for directed therapy with bioactive peptides and chemotherapy drugs may be an effective approach to treating gastric cancer (GC). We show genome-scale identification and characterization of differentially expressed lncRNAs in GC cells treated with a novel anti-cancer bioactive peptide (ACBP) and the chemotherapy drug oxaliplatin (ASLB). A total of 17,897 lncRNAs were identified through pairwise comparison, including 2,074 novel lncRNAs. Of those, 1,386 lncRNAs were differentially expressed (o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Furthermore, the ACBP treatment group exhibited significant differences in the regulatory mechanisms of gastric cancer cells compared with the OXA treatment group. The enrichment results of the AMPK metabolic pathway were consistent with those of lncRNA in MKN-45 cells treated with ACBP-OXA (20), suggesting a close relationship between the two. The AMPK signaling pathway mainly regulates cell metabolism and plays a key role in the regulation of cell energy homeostasis.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…Furthermore, the ACBP treatment group exhibited significant differences in the regulatory mechanisms of gastric cancer cells compared with the OXA treatment group. The enrichment results of the AMPK metabolic pathway were consistent with those of lncRNA in MKN-45 cells treated with ACBP-OXA (20), suggesting a close relationship between the two. The AMPK signaling pathway mainly regulates cell metabolism and plays a key role in the regulation of cell energy homeostasis.…”
Section: Discussionsupporting
confidence: 63%
“…Thus, current clinical research has been focusing on finding novel anticancer drugs with higher efficiency, lower toxicity and improved targeting ability. Previous studies have reported that ACBP combined with chemotherapy drugs (e.g., cisplatin and OXA) can inhibit the proliferation of MKN-45 cells, promote apoptosis and induce G2/M phase arrest (13,20). However, the mechanisms underlying the inhibitory effects of ACBP and chemotherapeutic drugs on cell growth remain largely unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Huang’s et al, study found that lncRNA LINC01269 may have a very important biological function, which is related to the OS rate and disease-free survival rate of patients with esophageal squamous cell carcinoma [ 41 ]. Han’s et al, study found that LINC01183 was the 10 most downregulated lncRNAs in gastric cancer cells [ 42 ]. In addition, The LncRNA and Disease Database (version 2.0) predicts that LINC01164 and LINC01269 are associated with a variety of cancers, such as non-small cell lung cancer and gastric cancer.…”
Section: Discussionmentioning
confidence: 99%